DISPUTABLE ISSUES OF THE CRITERIA FOR DIFFERENTIATING THE LEGISLATION SECTORS AND OBJECT OF THEIR REGULATION - M. F. Matyunin (Russian Journal of Economics and Law)
The article is devoted to determining of the criteria of differentiating of the legislation sectors, in particular, the criteria of complex sectors of legislation. Two criteria for extinguishing the complex legislation sector are defined: the state function and the type of public activity.